Expression and Visualization of Red Fluorescent Protein (RFP) in Neurospora crassa - Michael Freitag; Eric U. Selker (Fungal Genetics Reports, 2005)
We report the expression of Discosoma red fluorescent protein (RFP) and RFP fusion proteins in Neurospora crassa. RFP was expressed under the control of the Neurospora ccg-1 promoter in transformants with single copies integrated at the his-3 locus by gene targeting. Because this RFP gene, tdimer2(12), contains a 677 bp direct tandem repeat of dsRed, RFP constructs underwent RIP at high frequency in rid+ strains. Fusion proteins of RFP to the amino terminus of Neurospora heterochromatin protein 1 (HP1) were localized to heterochromatic foci in Neurospora nuclei, consistent with prior findings with carboxy-terminal HP1-GFP fusion proteins.